2015
DOI: 10.1039/c4cc09222h
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical synthesis of size-tailored hexagonal ZnS quantum dots

Abstract: ZnS quantum dots were synthetized at room temperature using a simple photochemical process involving ketyl radicals. Through the simple adjustment of reagent concentration, the method allows the control of nanoparticle size. Transmission electron microscopy confirmed that the nanomaterial adopts the hexagonal structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…24,25 Photons as a "traceless and green reagent" make the photochemical process greener and more sustainable. 26 For the past few years, photo-redox catalysis has made tremendous progress and widely been used in many aspects such as polycyclic addition and functionalization of organic substrates, 27 noble metal catalysis, [28][29][30] semiconductor synthesis, 31,32 carbon dioxide reduction, 33,34 polymer synthesis [35][36][37] and drug synthesis. [38][39][40][41] As far as we know, there has been no report on the photochemical synthesis of MoS 2 .…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Photons as a "traceless and green reagent" make the photochemical process greener and more sustainable. 26 For the past few years, photo-redox catalysis has made tremendous progress and widely been used in many aspects such as polycyclic addition and functionalization of organic substrates, 27 noble metal catalysis, [28][29][30] semiconductor synthesis, 31,32 carbon dioxide reduction, 33,34 polymer synthesis [35][36][37] and drug synthesis. [38][39][40][41] As far as we know, there has been no report on the photochemical synthesis of MoS 2 .…”
Section: Introductionmentioning
confidence: 99%
“…These methods are mostly expensive, time consuming and are not environmentally friendly . The photochemical method is a room temperature method for the synthesis of QDs . Marandi et al reported photochemical synthesis of CdS QDs .…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of Mn +2 ‐Doped ZnS Quantum Dots : Water‐soluble Mn 2+ ‐doped ZnS colloidal Qdots having orange colored (580 nm) emission were synthesized and purified in aqueous medium using a previously reported method . Typically, a mixture of 1 × 10 −3 m solution of manganese acetate tetrahydrate and 5.0 × 10 −3 m solution of zinc acetate dihydrate was continuously stirred in aqueous medium at 80–90 °C.…”
Section: Methodsmentioning
confidence: 99%